The System of Indicators of Economic Security of a Municipality as an Integral Element of a Multi-Level System of Economic Security - S. N. Mityakov; T. A. Fedoseeva; E. S. Mityakov (Мир новой экономики, 2021)
Ensuring economic security at all levels of the national economy is an integral part of ensuring national security. The article proposes a system of indicators for monitoring the economic security of municipalities, which can be adapted for any municipality and effectively used for comparative analysis of the levels of economic security of the territories under consideration, located at different hierarchical levels. We propose that the system includes 11 indicators and threshold values for each of them. We based our research on a systematic approach. The study involved dynamic, graphical analysis and economic and mathematical methods. This article is one of the first attempts to create a unified system of indicators for monitoring the economic security of municipalities.